High Resolution Genetic and Physical Mapping of a Major Powdery Mildew Resistance Locus in Barley - Hoseinzadeh, Parastoo; Zhou, Ruonan; Mascher, Martin; Himmelbach, Axel; Niks, Rients E.; Schweizer, Patrick; Stein, Nils (Frontiers in Plant Science, 2019)
Powdery mildew caused by Blumeria graminis f. sp. hordei is a foliar disease with highly negative impact on yield and grain quality in barley. Thus, breeding for powdery mildew resistance is an important goal and requires constantly the discovery of new sources of natural resistance. Here, we report the high resolution genetic and physical mapping of a dominant race-specific powdery mildew resistance locus, originating from an Ethiopian spring barley accession ‘HOR2573,’ conferring resistance to several modern mildew isolates. High-resolution genetic mapping narrowed down the interval containing the resistance locus to a physical span of 850 kb. Four candidate genes with homology to known disease resistance gene families were identified. The mapped resistance locus coincides with a previously reported resistance locus from Hordeum laevigatum, suggesting allelism at the same locus in two different barley lines. Therefore, we named the newly mapped resistance locus from HOR2573 as MlLa-H. The reported co-segregating and flanking markers may provide new tools for marker-assisted selection of this resistance locus in barley breeding.